Person-Centred Hepatitis C Virus Treatment In Community Settings - Davoud Pourmarzi (ACHSM, 2024)
The World Health Organization (WHO) has set a target to eliminate the Hepatitis C virus (HCV) as a public health threat by 2030. To achieve this, HCV treatment needs to be accessible through primary health care providers in community settings. In Australia, general practitioners and nurse practitioners can prescribe nearly free direct-acting antiviral (DAA) medication. However, there are still many barriers to the provision of HCV treatment in community settings. Considering the characteristics of HCV infection, people with HCV, and the Australian primary health system, person-centred HCV treatment is suggested to improve treatment uptake and adherence. Although the provision of person-centred HCV treatment in community settings is emphasised, the characteristics of these models are not well described. This short report describes the characteristics of person-centred HCV treatment in community settings to inform policy and practices in supporting HCV elimination. The characteristics were developed based on the analysis of findings of studies conducted by the author using person-centred care framework. The studies included a mixed methods systematic literature review, a Delphi study, and a mixed methods case study on a community-based model of care for treating HCV.